Effect of fat replacement in high internal phase emulsions constructed by high temperature saccharification of grafted proteins on gel properties and flavor profiles of sausages - Fei Lu; Yujie Chi; Yuan Chi (Poultry Science)
ABSTRACT: In order to mitigate the risk of cardiovascular diseases associated with excessive saturated fatty acid intake, utilizing high internal phase emulsions (HIPEs) as a substitute for animal fat in producing high-quality fat-substituted meat products is an ideal approach. This study involves the preparation of glycosylation products of egg white protein (EWP) through saccharification at high temperatures in the presence of fructooligosaccharides (FO). The resulting glycation products of EWP were employed to create colloidal particles, forming HIPEs, which were further utilized to induce the formation of HIPEs gels (HIPEs-Gs). The study investigated the effects of substituting different ratios (25%, 50%, 75%, and 100%) of animal fat with HIPEs and HIPEs-Gs on the gel properties and flavor characteristics of sausages. Results showed that, compared to the control group, substituting fat with HIPEs significantly improved the gel properties, cooking yield, and G′ of sausages, while excessive HIPEs-Gs substitution yielded negative effects. Low-field nuclear magnetic resonance results also demonstrated that adding HIPEs improved water and oil distribution in the sausage batter, enhancing protein's binding capacity with water. Scanning electron microscope revealed that HIPEs substitution led to a denser gel network with smaller pores, effectively “locking in” more water. Analysis of volatile compounds indicated accelerated release of aromatic compounds, alkanes, sulfides, and lipids when fat was substituted with HIPEs and HIPEs-Gs. Electronic tongue analysis suggested that HIPEs-Gs substitution reduced response values for umami and saltiness. In conclusion, compared to HIPEs-Gs, using HIPEs as a fat substitute improves the quality of sausages.